2022
DOI: 10.1186/s12974-021-02372-z
|View full text |Cite
|
Sign up to set email alerts
|

SNHG15 is a negative regulator of inflammation by mediating TRAF2 ubiquitination in stroke-induced immunosuppression

Abstract: Background Abnormal expression of long noncoding RNAs (lncRNAs) has been reported in the acute stage of acute ischemic stroke (AIS). This study aimed to explore differential lncRNA expression in the subpopulations of peripheral blood mononuclear cells (PBMCs) from AIS patients and further evaluate its underlying mechanisms in stroke-induced immunosuppression. Methods We reanalyzed lncRNA microarray data and investigated abnormally expressed lncRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In fact, we observed a radical decline in Bcl2l11 expression when Morrbid was upregulated ( Figure 7B ). Among the downregulated lncRNAs, eight had at least one citation; AI662270 , AU020206 , and Snhg15 were of particular interest ( Figure 7C ), as it has been reported that AI662270 and AU020206 are involved in the atherosclerosis induced by macrophages ( 33 , 34 ) and Snhg15 is involved in inflammation ( 35 ).…”
Section: Resultsmentioning
confidence: 79%
“…In fact, we observed a radical decline in Bcl2l11 expression when Morrbid was upregulated ( Figure 7B ). Among the downregulated lncRNAs, eight had at least one citation; AI662270 , AU020206 , and Snhg15 were of particular interest ( Figure 7C ), as it has been reported that AI662270 and AU020206 are involved in the atherosclerosis induced by macrophages ( 33 , 34 ) and Snhg15 is involved in inflammation ( 35 ).…”
Section: Resultsmentioning
confidence: 79%
“…In normal Chinese population, the levels of RDW range from 11.0 to 16.0%, and may increase under pathological conditions. It is well known that inflammatory response plays a prominent role on the pathophysiology of cerebrovascular disease ( 17 22 ). RDW may be associated with C-reactive protein, interleukin −6 and other inflammatory biomarkers ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circSCMH1 promotes translocation of obesity-associated protein into the endothelial cell nucleus via ubiquitination and subsequently facilitates m6A demethylation of Plpp3 mRNA and upregulates Plpp3 expression, thereby enhancing vascular repair after stroke in mice in vivo and in vitro ( 91 ). LncRNA SNHG15 suppressed K63-linked TRAF2 ubiquitination to improve acute ischemic stroke ( 92 ). Notably, in mouse ischemic stroke models (middle cerebral artery occlusion) in vivo , miR-181b expression is downregulated in response to ischemic exposure, thus ameliorating poststroke neurovascular injury by increasing ubiquitin carboxyl-terminal hydrolase isozyme L1 (UCHL1) and HSPA5 expression ( 93 ).…”
Section: Crosstalk Between Ubiquitin Ligases and Ncrnas Drives Vascul...mentioning
confidence: 99%